houghts about the influence of the French foresight in Latin America university planning. A literatura review. - Marcos Fernando Ruiz Ruiz, Marcos (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The study of the educational future through foresight is a research field of high projection and not fully developed in academia. This essay starts with a review of twenty-two found studies sources oriented to the future scenario planning about one dimension at the university; and particularly of the French prospective and its influence in the Latin American region. With this background, we explore the degree of the theoretical systematization between French prospective and university education, as well as propose a simple taxonomy that allows classifying the several methodologies founded in this complex field